Analysis of Government-Funded Research in Indonesia from 2014-2018: Implications for Research Trends in Science Education - Faisal, F.; Gi, G. M.; Martin, S. N. (Jurnal Pendidikan IPA Indonesia, 2020)
Government funding has the potential to increase research on particular topics that represent an integral focus of governmental policy. The reason is that researchers who seek funding from government sources need to target specific calls for research on topics that the government has identified as necessary for society. Analysis of funding trends can raise awareness about what topics are receiving adequate attention and can demonstrate how funding schemes may serve to limit (intentionally and unintentionally) researchers’ authority to design and manage projects and disseminate findings that are not financially supported by government funding agencies. In this study, we used a content analysis approach to analyze all projects awarded to the top five public teacher education institutions (TEIs) in Indonesia from 2014-2018. From the research project list from the five TEIs, we identified 225 science education projects for the sample of analysis. We extracted all keywords (nouns and adjectives) from the research project titles and grouped all extracted keywords into four categories: research topic, research subject or context, research product and outcomes, and content target. From the analysis, we offer some educational context for why scientific literacy and character and values education have emerged as such prominent topics in Indonesia, and we highlight the importance of greater involvement of teachers in research projects, the significance of research outcomes for improving science teaching and learning in schools, and the need to promote research on pedagogical coursework.